CONTRIBUIÇÃO AO CONHECIMENTO QUÍMICO DOS METABÓLITOS SECUNDÁRIOS DE TRÊS ESPÉCIES BACCHARIS DA SEÇÃO CYLINDRICAE: Baccharis pentodonta, Baccharis tridentata e Baccharis rufescens - Simioni, Raquel Endler (2013)
This research aimed to chemically study the secondary metabolites from inflorescences and leaves of male and female specimens of three species from the genus Baccharis: B. rufescens, B. pentodonta and B. tridentata. The plant materials were hydrodistilled for the collection and analysis of the obtained essential oils by GC/MS/FID, UV-Vis, IR and 1H and 13C NMR. The column chromatographic fractionation of the essential oil from male specimens of B. rufescens led to the isolation of two sesquiterpene alcohols, namely spathulenol and (E)-nerolidol, and the ketone 4,7(11)-amorphadien-8-one, which was obtained for the first time making it possible to study its structure using 2D NMR techniques. The essential oils of female specimens of B. rufescens were analyzed by 13C NMR, confirming the presence of (E)-nerolidol and the absence of the mentioned ketone. The oils of male and female specimens of B. pentodonta were very similar, presenting the major sesquiterpenes spathulenol, epiglobulol, viridiflorol, (+)-torreyol and α-cadinol. Likewise, the compositions of the essential oils from male and female specimens of B. tridentata were very similar, showing spathulenol as the major component, followed by caryophyllene oxide and (+)-torreyol. The aqueous extract remaining after the steam distillation of essential oils from B. tridentata was subjected to extraction with chloroform and then with ethyl acetate at pH 8 and pH 4. The extract obtained with ethyl acetate at pH 8 was analyzed by UV-Vis and shift reagents were added, making it possible to observe the presence of a flavanone whose 1H and 13C NMR spectra indicate that this substance is eriodictyol. The extract was chromatographed on a column of silica and structure of eriodictyol was carried out by UV-Vis, IR and 1H and 13C NMR. The ethyl acetate extract at pH 4 was analyzed by UV-Vis and 1H and 13C NMR, verifying the likely presence of 3-caffeoylquinic acid, 3,5-dicaffeoylquinic acid and 4,5-dicaffeoylquinic acid.